A situation of ethical limbo and preimplantation genetic diagnosis - Żuradzki, Tomasz (Journal of medical ethics, 2014)
I start with a brief information about the context of my previous paper1 since it is relevant for this discussion and, as Xavier Symons notices, I am ‘a bioethicist in a country where the statements of the Catholic Church have significant impact on medico-ethical policy.’2 In 2012, the Bioethics Committee of the Polish Academy of Sciences produced an Opinion calling for the regulation of preimplantation genetic diagnosis (PGD) (now it is not regulated but practiced).3 Some members of the Committee objected to the Opinion invoking their pro-life views. If their position were accepted by the legislator, PGD would be illegal, although in vitro fertilization (IVF), prenatal diagnosis and the termination of pregnancy in some rare cases (eg, when there is a great probability that a future child will suffer from an irreversible and serious disease) are legal. This could lead to absurd situations when an embryo implanted during the IVF procedure could be legally aborted because of genetic illness that could have been tested during PGD. I assumed that this legal solution would be hard to be acceptable for everyone, no matter which moral views she or he subscribes to. So I proposed a universal argument claiming that if IVF is legal and practiced, there is no moral ground to object legalisation of …